Comparison of ballistic performance of Dyneema®, hardened tool steel & alumina composite for low and medium velocity impact: a numerical approach - Harsh Navangul; Kushagra Kumar; Davidson Jebaseelan; Awani Bhushan; Devendran Thirunavukkarasu; Rajnish Mallick; Sandip Saha; Bisheshwar Haorongbam (Composites Part C: Open Access)
Human safety is the one of the most crucial aspects in defence industry. Every life matters therefore to protect a person from bullet impact it is of utmost importance to study bullet armour. Traditionally, these armour plates were made up of steel, aluminium, and recently, various fabrics like Ultra High Molecular Weight Polyethylene (UHMWPE), Kevlar, Twaron etc are reinforced with materials like steel, carbon fiber, ceramics etc. The present work studies ballistic composite of viz., Dyneema®, hardened tool steel and alumina that is light in weight, easy to manufacture, has high strength, and less damage at medium velocity profiles for a standard sized bullet. The armour composite plates were designed by varying their layer wise composition and thickness. A standard sized bullet of diameter 7.62 mm was impacted on them with two velocities: 200 m/s and 300 m/s. The various composite designs were composed of Dyneema® (UHMWPE), Hardened tool steel (HTS) & Alumina. It was found that the plate with composition of Dyneema® reinforced with HTS was able to stop the bullet in lesser time in comparison to the plate which had Dyneema®-Alumina-HTS composition. But on the other side the Dyneema®-HTS-Alumina composite was found out to be lighter in weight. The strength and hardness of HTS plays a major role in the Dyneema® reinforced HTS with bullet facing material (UHMWPE) absorbing the required bullet energy. For higher velocity the 9.5 mm configuration of Dyneema® with HTS is recommended but for lower velocity 5 mm configuration would suffice. The outcome of the current work is very much beneficial to various defence technologies.